Aspek Aspek Identitas Sosial dalam Self dan Gender : Studi Kasus Identitas Gender Mahasiswa UINSU dalam Penggunaan Media Sosial - Ainul Mardiyah; Muhammad Dzaki Fadhilla; Azizatuzzahra Azizatuzzahra (STIKes Ibnu Sina Ajibarang, 2025)
Social media has become a significant new space for the formation and expression of gender identity, particularly among adolescents and university students. This study aims to examine how students at the State Islamic University of North Sumatra (UINSU) perceive gender identity and express it through social media. Using a descriptive qualitative approach and case study method, data were collected through in-depth interviews with four students from diverse backgrounds. The findings indicate that social media provides a flexible and relatively safe space for students to express their gender identities, both explicitly and implicitly. Factors such as social environment support, self-awareness, and control over digital interactions play a crucial role in shaping their comfort in self-expression. This study highlights the importance of digital literacy and supportive social environments in accompanying the process of gender identity formation in the digital age.